How words mean lexical concepts, cognitive models, and meaning construction - Evans, Vyvyan (Oxford linguistics, 2010)
'How Words Mean' introduces a new approach to the role of words and other linguistic units in the construction of meaning. It addresses the interaction between non-linguistic concepts and the meanings encoded in language, developing an account of how words are understood when we produce and hear language in situated contexts of use.